Relación entre historia de la filosofía y filosofía teorética - Leocata, Francisco (Sapientia, 2014)
This article, after reviewing the different ways to tell the history of philosophy, focuses on the relationship between both aspects: theoretical philosophy and history of philosophy. Taking a critical distance both of conception that independent history of the work of truth seeking theoretical, as in the identification of both directions, thesis that took shape mostly from Hegel’s philosophy. The author proposes a hermeneutics application in reading the philosophical past, to open new questions and horizons in the real world and the demands and challenges of the historical era itself. Moreover, such hermeneutics, in turn, does not slide into relativism, but confirms the continuity of truth in its rich persistence over time.